Proteomics Mapping of the ISGylation Landscape in Innate Immunity - Thery, Fabien; Eggermont, Denzel; Impens, Francis (Frontiers in Immunology, 2021)
During infection, pathogen sensing and cytokine signaling by the host induce expression of antimicrobial proteins and specialized post-translational modifications. One such protein is ISG15, a ubiquitin-like protein (UBL) conserved among vertebrates. Similar to ubiquitin, ISG15 covalently conjugates to lysine residues in substrate proteins in a process called ISGylation. Mice deficient for ISGylation or lacking ISG15 are strongly susceptible to many viral pathogens and several intracellular bacterial pathogens. Although ISG15 was the first UBL discovered after ubiquitin, the mechanisms behind its protective activity are poorly understood. Largely, this stems from a lack of knowledge on the ISG15 substrate repertoire. To unravel the antiviral activity of ISG15, early studies used mass spectrometry-based proteomics in combination with ISG15 pulldown. Despite reporting hundreds of ISG15 substrates, these studies were unable to identify the exact sites of modification, impeding a clear understanding of the molecular consequences of protein ISGylation. More recently, a peptide-based enrichment approach revolutionized the study of ubiquitin allowing untargeted discovery of ubiquitin substrates, including knowledge of their exact modification sites. Shared molecular determinants between ISG15 and ubiquitin allowed to take advantage of this technology for proteome-wide mapping of ISG15 substrates and modification sites. In this review, we provide a comprehensive overview of mass spectrometry-based proteomics studies on protein ISGylation. We critically discuss the relevant literature, compare reported substrates and sites and make suggestions for future research.